Partitioning for a Concept-Based SoC Design to Address Product Evolution - Ahmed, Waseem; Tazuddin, Adrus Mohamad; Wong, Ming Ming; Liaw, Tzy Renn; Myers, Douglas (2007)
To address change encountered during product evolution in SoCs, a concept based design methodology based on UML 2.0 is presented in this paper. A system specification given in the form of UML 2.0 sequence and class diagrams is segregated into concepts with a Generic Adaptive Layer (GAL) around them. GALs offer generic adaptibility to existing concepts and change localization during product evolution. The major advantage of using the presented methodology is an improvement in the development time of the system during both the design and the maintenance phases. Experiences from using three categories of concepts are presented.